Acute pancreatitis and its association with dyslipidemia - Gudas Ravinder; Ramchandraiah Chintalaboguda; Sanjeev Kumar Adepu (Asian Journal of Medical Sciences, 2022)
Background: Pancreatitis is described as any inflammation that manifests in acute or chronic forms in the pancreas. Acute pancreatitis (AP) is a quick attack that results in pancreatic inflammation and affects the peripancreatic tissue and surrounding organ. Aims and Objectives: This study aims to evaluate lipid profile tests in AP patients. Materials and Methods: The present study was conducted in the Department of General Surgery, Government Medical College, Nizamabad, India, prospectively from July 2019 to May 2022. In our study, we enrolled 100 patients between the age of 20 and 60 and divided them into two groups by random selection. We chose 50 consecutive cases of pancreatitis for the study group and 50 other hospitalized patients for the control group. Results: Mean age of the case group and control group was found to be 39.17±7.42 and 41.92±9.1, respectively. We observed that the peak incidence of pancreatitis occurred between the ages of 40 and 70, with a male predominance in all age categories. When compared to control, low-density lipoprotein cholesterol (P=0.715), total cholesterol (P=0.3124), high-density lipoprotein cholesterol (HDL-C) (0.164), non-HDL-C (0.2436), and triglyceride (P=0.1266) of the study group were found to be statistically non-significant. Conclusion: It is determined that serum lipid profile and pancreatitis are frequently linked. To reduce the risk of developing this disease, prevent its underlying complications, and manage the possibility of subsequent recurrences, patients with the aforementioned risk factors should be assessed for any changes in their serum lipid profile. If such an alteration is discovered, they should be treated with antilipidemic medications, dietary modification, lifestyle change, and physical activity.